PEMODELAN REKONFIGURASI JARINGAN SPINDLE DISTRIBUSI 20 KV BERBASIS SCADA UNTUK MENINGKATKAN EFISIENSI SISTEM DISTRIBUSI - Sopian, Yayan; Damiri, Dhami Johar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growth of national electricity consumption, particularly in urban areas such as Jakarta, demands an efficient and reliable distribution system. The main challenges is the high level of technical losses, which reduces operational efficiency. This study develops a network reconfiguration model for a 20 kV spindle distribution system based on Supervisory Control and Data Acquisition (SCADA) to improve distribution efficiency. Reconfiguration is performed by automatically adjusting switch positions through SCADA to optimize real-time power flow. The study focuses on the GH272 spindle network in Central and West Jakarta, consisting of 15 feeders with varying load characteristics. System modeling was conducted using DIgSILENT PowerFactory, utilizing load data obtained from SCADA sensors and optimization through the Simulated Annealing (SA) algorithm. Simulation results over a 24-hour period indicate a reduction in power losses from 1.15 MWh to 0.97 MWh, (decrease 15.65%), with daily energy savings of 179 kWh (equivalent to IDR 258,601 per day). These results demonstrate that SCADA enhances distribution efficiency and supports an adaptive distribution system. The study recommends strengthening infrastructure by deploying additional sensors such as ADCU and integrating the Meter Data Management System (MDMS) with the Advanced Distribution Management System (ADMS) to enable more responsive decision-making.